Adversity-hope hypothesis: Air pollution raises lottery demand in China - Soo Hong Chew; Haoming Liu; Alberto Salvo (Journal of Risk and Uncertainty, 2021)
The empirical literature points to a stylized phenomenon of increased demand for hope following adversity. Clotfelter and Cook (1989) suggest that hope is a key sentiment underpinning recreational gambling. Chew and Ho (1994, this journal) offer the view of hope being experienced in lottery products when people enjoy delaying the resolution of uncertainty. Taking air quality as an indicator of subjective well-being, we hypothesize a positive causal relationship between air pollution and lottery sales. We test this hypothesis using data from China and find that air pollution measured by particle concentration increases demand for a popular lottery for which province-level daily sales records exist. The relationship can readily be seen on combining high-frequency, spatially resolved lottery sales and particle pollution data. Our findings support the adversity-hope hypothesis in the context of air quality and lottery sales and point to further tests using other measures of adversity and proxies of demand for hope.
Keywords: D12; D91; D81; G41; H23; L83; Q51; Q53; 300; Adversity; Hope; Attitudes toward risk and hope; Environmental degradation; Air pollution; Lottery demand; Particulate matter; Haze; Smog; Instrumental variables